Purification and biochemical properties of an N-hydroxyarylamine O-acetyltransferase from Escherichia coli - Yamamura, Ei-Tora; Sayama, Michio; Kakikawa, Makiko; Mori, Masa-aki; Taketo, Akira; Kodaira, Ken-Ichi (Biochimica et biophysica acta, 2000)
The N-hydroxyarylamine O-acetyltransferase of Escherichia coli has been expressed as a histidine tagged fusion protein and purified using immobilized nickel column chromatography. The molecular mass of the histidine tagged N-hydroxyarylamine O-acetyltransferase was estimated to be 60.0 kDa by gel filtration and 34.0 kDa by SDS–PAGE and DNA sequence, suggesting that the native enzyme exists as homo dimer. The catalytic properties were investigated using o-aminobenzoic acid as a substrate. No difference in acetyltransfer activity was observed between histidine tagged protein and untagged enzyme. Kinetic studies indicated a ping-pong bi bi mechanism of the catalysis. Inhibition by N-ethylmaleimide and salicylic acid was competitive with o-aminobenzoic acid and non-competitive with acetyl-CoA.